Effect of Integrated Use of Farmyard Manure and Chemical Fertilizers on Soil Properties and Productivity of Rice in Chitwan - Lamichhane, Sarita; Khanal, Babu Ram; Jaishi, Ajay; Bhatta, Sandesh; Gautam, Roshana; Shrestha, Jiban (Agronomy Journal of Nepal, 2022)
The effect of sole application of farm yard manure (FYM) and combined application of chemical fertilizers and FYM on soil properties and growth and yield traits of rice (Variety: Ramdhan) was studied on sandy loam soil at Rambagh, Chitwan, Nepal from June to November 2019. The seven treatments were studied in a randomized complete block design with four replications: T1: 100% recommended dose of inorganic fertilizer (RDIF) (i.e., 100:60:40 NPK kg ha-1); T2: 50% RDIF+ FYM @ 9.9 Mt ha-1; T3: 50% RDIF+ FYM @ 31.3 Mt ha-1; T4: 50% RDIF+ FYM @ 11.05 Mt ha-1; T5: FYM @ 19.83 Mt ha-1. The results indicated that combined application of chemical fertilizers and farmyard manure was found to have a significant effect on the number of effective tillers per m-2 and grain yield of rice. There was no significant interaction between thousand grain weight and sterility percent. The highest grain yield of 3,453.69 kg ha-1 and the highest number of effective tillers per m-2 (299) were found in the application of 50% RDIF+ FYM @ 31.3 Mt ha-1. The application of the highest level of FYM alone improved the soil properties. The highest values of available soil organic carbon (34.67 Mt ha-1), available soil nitrogen (1.24 Mt ha-1), and available soil phosphorus (39.57 kg ha-1) at a depth of 0–15 cm were found with the application of FYM @ 62.5 Mt ha-1. The findings of this study suggest that farmers can apply FYM @ 62.5 Mt ha-1 to improve soil properties and 50% RDIF + FYM @ 31.3 Mt ha-1 to have the higher grain yield of rice.